Corrigendum to "Anatomical normality and variability: Historical perspective and methodological considerations" [Transl. Res. Anat. 23C (2021) 100105] - Andrzej Żytkowski; R. Shane Tubbs; Joe Iwanaga; Edward Clarke; Michał Polguj; Grzegorz Wysiadecki (Elsevier, 2022)
Purpose: The aim of this review is to reflect on the question of gross anatomical normality and variability. Particular attention has been paid to what is considered normal in gross anatomy and the premises for recognizing a given structure as normal. The earliest historical sources referring to anatomical variations are described in the paper. The general significance of anatomical variations is also discussed. Results: Having established and classified the laws of nature, scientists gradually achieved the skill of judging what is most typical and what is rare or deviates from the commonly-observed pattern. Normality in anatomy can be considered relative (linked to a specific set of assumptions) and is inferred from numerous repeated observations. In anatomy textbooks, the term "norm" is associated with such concepts as general pattern, rule, or canon. Deviations from the most common (assumed to be typical) morphology are described as variants or types of organs or anatomical structures. The term "anomaly" is also used in the anatomical and medical literature to describe variations; however, this designation can also be applied to pathological conditions. Nevertheless, the "norm" in anatomy is not as precise a concept as one would wish, and can be considered an approximation. In fact, anatomical variability is the rule, though most variations are within the normal range. Thus, the idea of a medical and anatomical norm is analogous the sorites paradox because the boundaries between what is considered normal and what is anomalous are blurred. Nevertheless, the anatomical norm should only be regarded as an idealized scientific model; anatomical variations should be kept in mind in clinical practice. Conclusions: "Anatomical norm" can be considered on the one hand as a useful reference point for clinicians and on the other as an idealized scientific model.